Blood carotenoids as a biomarker of intestinal functionality and performance in broiler chickens - Bittencourt, Letícia Cardoso; Silveira, Robson Mateus Freitas; Menten, José Fernando Machado (Frontiers in Physiology, 2025)
BackgroundResearch to establish a reliable biomarker that allows the practical and accurate evaluation of intestinal functionality and productive performance in broiler chickens is one of the main challenges in modern poultry production. In this context, blood carotenoids have stood out as promising indicators, as they reflect the absorptive efficiency and physiological balance of birds. The objective of this study was to verify whether the determination of total carotenoids in the blood can be used as an effective biomarker in experiments that evaluate nutritional additives, correlating them with zootechnical parameters.Materials and MethodsData from five experiments were analyzed, totaling 9,125 broilers. Performance traits and blood total carotenoids were measured, and univariate and multivariate analyses were applied to evaluate the relationships between carotenoid status and performance.ResultsSupplementation with nutritional additives resulted in a mean increase of 14% (p < 0.05) in blood carotenoid concentrations, regardless of the experimental design, diet, or the presence of a health challenge. A positive correlation was also observed between carotenoid levels and weight gain, and a negative correlation with feed conversion, during the periods from 0 to 35 and 0 to 42 days of age.ConclusionThe results indicate that the quantification of carotenoids in the blood, performed in a fast and minimally invasive way, can be used as an innovative tool to monitor intestinal functionality and predict productive performance in broilers in response to nutritional supplementation.